Effects of the application of α1- and α2-adrenoceptor agonists and antagonists into the ventromedial hypothalamus on the sodium and potassium renal excretion - Saad, W. A.; Camargo, L. A A (Karger Publishers, 1984)
The effects of sodium and potassium excretion after intrahypothalamic administration of two α-adrenoceptor agonists and the effect of α-adrenoceptor antagonists were studied in groups of rats. Prazosin was equally effective at blocking the natriuretic and kaliuretic responses to the α1-adrenoceptor agonist phenylephrine and the mixed α1/α2-adrenoceptor agonist noradrenaline, while yohimbine which acts preferentially on α2-adrenoceptors was effective in potentiating these responses. These results suggest the presence of two types of α-adrenoceptors for the modulation of ventromedial hypothalamic pathways that interfere with the regulation of the two cations: stimulation of α1-adrenoceptors facilitates, while stimulation of α2-adrenoceptors inhibits the excretion of the ions.
Keywords: alpha 1 adrenergic receptor; alpha 2 adrenergic receptor; alpha adrenergic receptor stimulating agent; noradrenalin; phenylephrine; prazosin; yohimbine; animal experiment; central nervous system; kidney; nonhuman; potassium urine level; rat; sodium urine level; zona incerta; Adrenergic alpha-Agonists; Adrenergic alpha-Antagonists; Animal; Dogs; Dose-Response Relationship, Drug; Hypothalamus, Middle; Norepinephrine; Phenylephrine; Potassium; Prazosin; Rabbits; Rats; Sodium; Support, Non-U.S. Gov't; Yohimbine